2016
DOI: 10.1140/epjc/s10052-016-4030-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding internal backgrounds in NaI(Tl) crystals toward a 200 kg array for the KIMS-NaI experiment

Abstract: The Korea Invisible Mass Search (KIMS) collaboration has developed low-background NaI(Tl) crystals that are suitable for the direct detection of WIMP dark matter. Building on experience accumulated during the KIMS-CsI programs, the KIMS-NaI experiment will consist of a 200 kg NaI(Tl) crystal array surrounded by layers of shielding structures and will be operated at the Yangyang underground laboratory. The goal is to provide an unambiguous test of the DAMA/LIBRA annual modulation signature. Measurements of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 32 publications
4
66
0
Order By: Relevance
“…These background levels are lower than those of the crystals used by the NAIAD experiment [32], but higher than those in DAMA/LIBRA [9]. The higher background in is primarily due to a larger contamination of 210 Pb [19,25]. Detailed background studies of these crystals are reported elsewhere [19,25,26,35].…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…These background levels are lower than those of the crystals used by the NAIAD experiment [32], but higher than those in DAMA/LIBRA [9]. The higher background in is primarily due to a larger contamination of 210 Pb [19,25]. Detailed background studies of these crystals are reported elsewhere [19,25,26,35].…”
Section: Methodsmentioning
confidence: 93%
“…The Korea Invisible Mass Search (KIMS) collaboration has developed low-background NaI(Tl) crystals for the purpose of reproducing the DAMA's modulation results [19,25]. A good understanding of the residual radioactive background contaminants of the crystals has been achieved [26].…”
Section: Size (D)×(l)mentioning
confidence: 99%
“…Several experiments have been trying to confirm or refute the DAMA/LIBRA annual modulation, including ANAIS, DM-Ice, KIMS and COSINE [7][8][9][10]. However, none of these efforts have achieved a background low enough to confirm or refute the modulation effectively within a reasonable amount of time, and the biggest source of background comes from radioactive impurities inside the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…The COSINE-100 experiment [1] is a joint effort between KIMS-NaI [2][3][4] and DM-Ice [5,6] to unambiguously test the claim of dark matter detection by the DAMA/NaI [7] and DAMA/LIBRA [8][9][10] experiments with thallium-doped sodium iodide (NaI(Tl)) scintillating crystals. COSINE-100 is located at the Yangyang Underground Laboratory (Y2L), in the Yangyang pumped storage power plant, with 700 m minimum of rock overburden.…”
Section: Introductionmentioning
confidence: 99%